Die Grünen—A History of the Foundation of Germany's Green Party (KULT_online, 2011)
Silke Mende examines in her award-winning PhD thesis the origins of the Green Party during the 1970s. In the first part of her book she characterizes five social groups whose mentalities were crucial in the foundation of the party in 1980. In the second part she analyses how it came about that these extremely different groups were integrated into one party.